SNACK BAR SORGUM DAN KACANG MERAH RENDAH INDEKS GLIKEMIK SEBAGAI MAKANAN SELINGAN TINGGI SERAT PENDERITA DIABETES MELITUS - Rossa Rosefa Simanjuntak; Agus Sulaeman; Yenny Moviana; Judiono Judiono (Jurnal Gizi dan Dietetik, 2022)
The management of diet in diabetes is not only limited to restriction of calories and carbohydrate intake, but also must pay attention to other qualitative nutritional aspects such as glycemic index (IG) and fiber consumption. Adequate fiber consumption can help control blood glucose levels. Sorghum flour and red beans have a low glycemic index and high fiber content. The purpose of this study was to determine the effect of snack bars of sorghum flour and red beans on organoleptic properties and dietary fiber levels. This study used an experimental study design with the formulation of sorghum flour and red beans were 65%:35% (Formula1),  70%:30% (Formula 2), and  80%:20% (Formula 3), respectively. Quality testing was done by hedonic test and gravimetric enzymatic test for dietary fiber content testing in the most preferred formula. Results show there is a significantly difference in the aspect of taste, while in the aspect of color, aroma and texture there is no significantly difference. The fiber content of snack bar sorghum flour and red beans from formula 2 is 6.08 grams/100 grams.